The Gunadule People Through the Photographic Gaze of the Barefoot Carmelite Missionaries in the Apostolic Prefecture of Urabá, Colombia (1918-1941) - Díaz Baiges, David (2021)
From the end of the XIX century and during the XX there was a reactivation of missionary activity at a global level. In Colombia, this rebirth gave a leading role to the Catholic Church in the tasks of incorporating into the nation the indigenous populations that lived outside the State. The studies that analyze the role of the missions in the state advance towards «wasteland» territories in Colombia, have not considered the representations that the religious built on the native peoples that they had to «civilize». Through these, they classified these populations based on racial and cultural criteria that gave meaning to missionary action and, in turn, legitimized the new republican order. For this reason, in this article we want to analyze the representations that the barefoot Carmelite missionaries built on the gandule people of the gulf of Urabá region. To undertake this task, we will use some little worked sources, the photographs.